Calculus Help
posted by Tim .
Use logarithmic differentiation to find the derivative of the function. show steps please!
y=(e^xcos^2(x))/(x^2+x+1)

log y = log (e^x  xcos^2(x))  log(x^2+x+1)
1/y y' = (e^x  (cos^2 x  2xcosx*sinx))/(e^x  xcos^2 x)  (2x+1)/(x^2+x+1)
y' = (e^x  cos^2 x + xsin2x)  (2x+1)/(x^2+x+1)^2
If you want to put it all over the common denominator, it gets fairly messy on top. 
actually, I see I did forget to include a factor of 1/(x^2+x+1) in the first term. Dang!
Luckily, it's not my job to fix it!